Curriculum Reform Meets Classroom Realities: Selected Indonesian Teachers’ Perspectives on the Merdeka Curriculum - Kumayas, Tirza; Luntungan, Grace Shirley; Arsai, Alfons Napoleon; Tatipang, Devilito Prasetyo (REiLA : Journal of Research and Innovation in Language, 2025)
The introduction of the Merdeka Curriculum marks a transformative shift in Indonesia’s English Language Teaching (ELT) landscape by promoting flexibility, student-centered learning, and project-based approaches. However, the success of such curriculum reform relies heavily on how teachers, as frontline implementers, perceive, adapt, and navigate its complexities in diverse classroom realities. Addressing a critical gap in existing research that predominantly focuses on policy-level analysis, this qualitative case study investigates the lived experiences, perceptions, and coping strategies of Indonesian ELT educators amidst the early stages of Merdeka Curriculum implementation. Drawing on Fullan’s theory of educational change, data were gathered through semi-structured interviews, classroom observations, and document analysis involving 20 English teachers, 30 students, and 10 administrators across rural, suburban, and urban settings. Thematic analysis revealed that while the curriculum fosters innovation and autonomy, teachers face significant constraints including insufficient training, technological inequity, and excessive administrative demands. Despite these challenges, educators expressed strong support for student-centered instruction, multimedia integration, and skill development emphasizing communication and critical thinking. This study contributes uniquely by offering context-specific insights into teacher agency within systemic constraints, advocating for equitable resource allocation, professional development, and collaborative policy feedback mechanisms. By amplifying teacher voices, this research not only informs national curriculum design but also engages in broader global conversations on curriculum autonomy, pedagogical reform, and the essential role of teachers in enacting meaningful educational transformation.